Spatially Resolved Electrochemical Strain of Solid‐State Electrolytes via High Resolution Sequential Excitation and Its Implication on Grain Boundary Impedance. Issue 10 (1st September 2020) - Yu, Junxi; Duan, Shanshan; Huang, Boyuan; Jin, Hongyun; Xie, Shuhong; Li, Jiangyu
Abstract: Solid‐state electrolytes have great potential in solving the intrinsic safety issues of conventional lithium‐ion batteries utilizing liquid electrolytes, and there is a tremendous effort in developing solid‐state electrolytes with improved ionic conductivity via microstructure engineering spanning multiple length scales. Nevertheless, there still lacks an effective method to probe the local ionic conductivity at the nanoscale with sufficient resolution, and thus how the microstructure impacts macroscopic ionic conductivity of solid‐state electrolytes remains inadequately understood. Here, the newly developed sequential excitation (SE) electrochemical strain microscopy is applied to spatially resolve local electrochemical processes at the nanoscale, unraveling the ionic dynamics of grain boundary in Li1.3 Al0.3 Ti1.7 (PO4 )3 solid‐state electrolytes that correlate well with macroscopic impedance analysis. The high‐conductivity sample possesses comparable ionic dynamics at grain boundary and within grain interior, while low‐conductivity sample exhibits much higher resistance at the grain boundary, even though the conductivity of its grain interior is comparable to high‐conductivity sample. The study thus provides direct experimental evidence on the bottlenecking grain boundaries in ionic conduction, and offers a powerful tool to study local ionic dynamics at the nanoscale in one‐to‐one correspondence to the microstructure features. Abstract : The newly developed sequential excitation electrochemical strain microscopy is applied to spatially resolve electrochemical processes at the nanoscale, unraveling the ionic dynamics of grain boundary in Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP) solid‐state electrolytes that correlates well with macroscopic impedance analysis. This study offers a powerful tool to study local ionic dynamics at the nanoscale in one‐to‐one correspondence to the microstructure features.